Entre Ser e Tempo: Angústia, Temporalidade e Morte em Martin Heidegger - Fantin, Natan Júlio (2024)
This dissertation aims to deepen the investigation into the notion of affectivity in Being and Time by Martin Heidegger, focusing on the phenomenon of angst as a fundamental affective disposition that reveals the existential structure of Dasein in its relation to temporality and death, thereby guiding philosophical inquiry. The research is divided into three main chapters. The first chapter explores Heidegger’s concept of death, distinguishing between its improper understanding, rooted in everydayness, and its proper understanding, as the ultimate possibility of Dasein, confronting it with its finitude. This analysis establishes death as a fundamental horizon for understanding existence, suggesting that angst, by unveiling the imminence of death, illuminates the path to a more authentic existence. In the second chapter, the dissertation addresses Heidegger’s notion of temporality, emphasizing the temporal ekstases of future, having-been, and present. The analysis details how temporality shapes Dasein’s experience, demonstrating that angst is deeply rooted in Dasein’s temporal structure. The dissertation argues that angst, by revealing Dasein’s finitude, opens it to its most authentic possibilities and thus to a more authentic existence. The third chapter examines angst as an existential experience that confronts Dasein with nothingness, transcending traditional approaches of psychology and psychoanalysis. The dissertation discusses angst as a force that, by detaching Dasein from its everyday engagements, prepares it for an authentic resolution of its existence. Furthermore, it explores the relationship between angst and transcendence, suggesting that angst, by confronting Dasein with its finitude, plays a central role in the practice of philosophizing. Throughout the dissertation, phenomenology is employed as the primary method of investigation, enabling a rigorous and detailed analysis of angst without reducing it to psychologizing terms. The research concludes that angst, by revealing the temporal and finite structure of Dasein, is fundamental to understanding human existence in Heidegger’s thought. Thus, the dissertation offers a phenomenological interpretation that elucidates the relationship between angst, temporality, and death within the context of philosophical questioning.